Effect of the indenopyridine RTI-4587-073 (l) on feline testicle - D'Francisco, Florencia (2019)
The aim of this study was to describe the seminal, histomorphological and hormonal effects of the oral indenopyridine RTI-4587-073(l) on feline testicle. Clinical side effects were also recorded. Sixty testicles of 30 adult cats that had been treated (d 0) with RTI-4587-073(l) 12.5 mg/kg PO and randomly hemiorchiectomized twice on: day -14 (n = 8), 6 h (n = 6), 12 h (n = 8), 24 h (n = 6), day 7 (n = 8), day 14 (n = 6), day 21 (n = 6), day 35 (n = 6) or day 42 (n = 6) were studied. Before each hemiorchiectomy, fecal samples for testosterone (T) measurement were collected and the testes were grossly and ultrasound examined. This indenopyridine did not cause changes in testicular weight (P > 0.1), volume (P > 0.1), echostructure, gonadosomatic index (P > 0.1), fecal T concentrations (P > 0.1), nor clinical side effects. A severe disorganization of the cytoarchitecture of the seminiferous epithelium, sloughed cells and fluid, were observed in the 6 h samples up to a maximum at 24 h. Tubular diameter (P < 0.01) increased twice, during the first 24 h and on d 35. Germinal epithelium achieved its minimum height on d 14 to rapidly recover thereafter. This treatment caused a significant decrease in the volume of all the seminiferous cell components, except spermatogonias. All histotological parameters normalized by the end of the study. It was concluded that RTI-4587-073(l) severely disrupted spermatogenesis during the first 24 h after treatment returning to normality in approximately one spermatic cycle without clinical side effects.